Europium(III) and gallic acid ligand coordination compounds: synthesis, characterization, photophysical processes, and optimization of luminescent properties - Moralles, Vagner Antônio [UNESP]; Davolos, Marian Rosaly [UNESP]; Cebim, Marco Aurélio [UNESP] (Elsevier, 2023)
We obtained EuIII, GdIII, and GdIII doped with EuIII (1 at.% and 5 at.%) complexes with the ligand derived from 3,4,5-trihydroxybenzoic acid (H4Gal). Synthetic routes are proposed from acetate and chloride solutions of the trivalent lanthanides. We demonstrated the decomposition of the ligands 3,4,5-trihydroxybenzoate (H3Gal ≡ L–) and 3-hydroxo-4,5-dihydroxybenzoate (H2Gal2– ≡ L’2 –) in an acetic solution medium. [LnLL’(H2O)2] complexes are obtained in a metal chloride solution medium. We studied the complexes in the solid state. We described the photophysical processes in the complexes, and they resulted in an energy diagram of the EuIII compounds in which the position of the states related to the LMCT transition are intermediate to the ligand's singlet (S1) and triplet (T1) states. We obtained the position of the triplet state (T1) from the luminescence of the GdIII complex. We performed the calculations of the EuIII complex's electronic structure using the Lumpac software to confirm the propositions obtained through experiments. The proposition is that the excitation in the LMCT state rapidly populates the T1 state, and the L–L’2 –→EuIII back energy transfer may occur. One of the possible disadvantages of the complexes is the enormous non-radioactive deactivation due to the oscillators (O–H) and (C–H). The EuIII characteristic luminescence is of little intensity. We obtained GdIII compounds doped with EuIII at 1.0 and 5.0 at.% to optimize luminescent properties. We obtained the emission and excitation spectra of the complexes at 77 and 17 K, showing ligands' phosphorescence superimposed on the characteristic emissions 5D0 →7FJ (J = 0–4) of the EuIII ion.
Keywords: Coordination nanoparticles; Europium(III); Gadolinium(III); Gallic acid; LMCT; Luminescence